Chelation, Characterization and Antimicrobial Screening of Some Mixed Antituberculosis–Vitamin Metal Drug Complexes - Bamigboye, M.O.; Obaleye, J.A.; Lawal, A.; Babamale, H.F.; Ajibola, A.A.; Adimula, V.O.; Lawal, M. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2017)
In this study, mixed Zn(II), Cu(II), Co(II) complexes of Isoniazid and vitamin C were synthesized and characterized by melting point, conductivity measurement, Fourier Transform Infra-red (FT-IR), Atomic Absorption Spectroscopy and elemental analyses. The bonding nature of the mixed parent ligands and the structure of the complexes were based on analytical and spectroscopic techniques. The complexes were proposed to have the formula [M1L1L2(Cl2)], [M2L1L2(SO4)], [M3L1L2(Cl2)] where M1 = Zn(II), M2 = Cu(II), M3= Co (II) L1= Isoniazid and L2 = Vitamin C. The infra-red data relate to the results of the most informative and indicative region. The result of spectra data confirmed that the two ligands were bidentate in their mode of coordination with the metal ions. The complexes are in octahedral geometry and the molar conductance was found to be non-electrolytic in nature. Antimicrobial test was carried out against four bacterial species namely Bacillus subtilus, Staphylococuss aureus, Escherichia coli and Pseudomonas aeroginosa. All the complexes showed higher antibacterial activity at the same concentration against the microorganisms used compared to the ligands.